Analisis Problematika Pembelajaran Daring Pada Pendidikan Karakter di Era Pandemi (Studi Kasus MI Al-Hikmah Sidoarjo) - Tungga Purnama Sari; Reny Masyitoh; Millatus Shofi; Khanifatus Sholikhah; Mazaya Li Azlina (IAI Al Khoziny Buduran Sidoarjo, 2022)
This paper aims to find out the problems of online learning on student character education in the pandemic era in the case study of MI AL-HIKMAH Sidoarjo. By using the literature review method, namely by tracing various kinds of reference sources critically in order to get good and accurate data when explaining and explaining the topic of discussion, in this study a survey was also conducted at MI Al-Hikmah on student interaction and interest in online learning, problematic is a problems or complaints that occur in online or online learning, meanwhile, character education is a manifestation of the achievement of a generation that is intelligent and has good character and personality and will be useful for the Indonesian nation. An education is said to be successful, judging by how well the characters formed can balance cognitive, affective and psychomotor skills to become a good person, in the midst of a pandemic like this, education that was originally offline has turned into online. This study uses a qualitative descriptive study with literature that provides an overview of the solutions to online learning problems for the character education of students in elementary schools. Changes in character education in students during online learning occur due to problems that arise during online learning itself. The problems that arise are reduced teacher and student interactions, the level of educator response to teacher and student interactions during online learning states as many as 34% of students are less interactive and respond online learning, as many as 32% of students responded quite well, as many as 26% of students responded well, the linkage of MI Al Hikmah Sidoarjo students from the survey observed stated that 50% of students were less interested in online learning, 25% were quite interested, 19% not at all interested and 6% interested. This is due to the lack of supporting facilities for online learning, and students' motivation towards online learning is less supportive because the surrounding environment is less supportive. Families and parents must support online learning facilities.